2020
DOI: 10.1186/s42466-020-00062-4
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography-based assessment of retinal vascular pathology in cerebral small vessel disease

Abstract: Background Cerebral small vessel disease (CSVD) is a disorder of brain vasculature that causes various structural changes in the brain parenchyma, and is associated with various clinical symptoms such as cognitive impairment and gait disorders. Structural changes of brain arterioles cannot be visualized with routine imaging techniques in vivo. However, optical coherence tomography (OCT) is thought to be a “window to the brain”. Thus, retinal vessel parameters may correlate with CSVD characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
4
11
0
Order By: Relevance
“…The median number of CSVD patients per study was 262 (range 24–4395) and the median number of controls per study was 814 (range 20–10158). We identified 10 reports using fundus photography [ 21 30 ], one study using OCT [ 52 ], one using OCTA [ 59 ], and one combining OCT and OCTA [ 51 ]. We found no report leveraging VF assessment, FA or ERG to investigate sporadic CSVD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median number of CSVD patients per study was 262 (range 24–4395) and the median number of controls per study was 814 (range 20–10158). We identified 10 reports using fundus photography [ 21 30 ], one study using OCT [ 52 ], one using OCTA [ 59 ], and one combining OCT and OCTA [ 51 ]. We found no report leveraging VF assessment, FA or ERG to investigate sporadic CSVD.…”
Section: Resultsmentioning
confidence: 99%
“…A single large study [ 26 ] reported higher prevalence among CSVD patients (compared to healthy controls) of RNFL wedge-shaped defects on fundus photography, a semi-quantitative marker of focal nerve fiber damage [ 69 ]. Regarding OCT imaging, one study [ 51 ] reported no associations with retinal measurements, while another [ 52 ] reported increased arteriolar thickness, quantified as Mean Wall Thickness (MWT) or Wall-to-Lumen Ratio (WLR), among CSVD patients compared to controls. The latter report also identified an association between arteriolar WLR and WMH severity on MRI, as well as with select cerebrospinal fluid biomarkers.…”
Section: Resultsmentioning
confidence: 99%
“…The strengths of this study include the thorough screening for concurrent neurological or ocular comorbidities, the use of high-resolution MRI, a complete ophthalmic assessment, the use of state-of-the-art high-resolution SD-OCT imaging including novel read-outs corrected for ocular anatomy such as MRW and the use of standardized and published automated image analysis for both MRI and OCT. To date, this study is the first to investigate structural retinal changes considering all layers assessed by OCT in patients with CSVD after few studies assessed single-layer structural changes or structural and flow changes within the retinal vasculature 38 , 42 44 . The limitations of our study include foremost its relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al 25 recently reported a vessel density reduction in the superficial retinal capillary plexus in CSVD patients but did not consider any choroidal parameters either. Abdelhak et al 26 used structural OCT data to assess the retinal arterioles in individuals with stroke secondary to sporadic CSVD. They identified an increase in ratio between wall and lumen ratio in patients with CSVD, supporting that the retinal vasculature is altered www.nature.com/scientificreports/ in CSVD.…”
Section: Discussionmentioning
confidence: 99%